KONSEP TEORI ETNOMETHODOLOGI DALAM PENDIDIKAN ISLAM: SEJARAH MUNCULNYA TEORI ETNOMETHODOLOG, KONSEP DASAR, TOKOH-TOKOH DAN IMPLEMENTASI TEORI DALAM PENDIDIKAN ISLAM - Zainal, Afdhal; Darmawansyah (Musawa: Journal for Gender Studies, 2021)
Ethnomethodology is the study of everyday practices carried out by members of society in everyday life. Actors are seen to do their everyday life through various kinds of ingenious practices. Ethnomethodology develops in various ways. The two main types are institutional studies and conversational analysis. Ethnomethodology has a different perspective from structural and interactionist theories in viewing social reality. As explained above, structural theory sees the most significant picture of human social life in the external forces that compel the individual. Therefore, to understand social behavior, an understanding of structural determination in human life must be developed. Meanwhile, for interactionists, actors (individuals) are viewed as priority objects. So, this theory builds a comprehension by first understanding individual social actions.